Cyclin A triggers mitosis either via the greatwall kinase pathway or cyclin B - Hégarat, N; Crncec, A; Suarez Peredo Rodriguez, MF; Echegaray Iturra, F; Gu, Y; Busby, O; Lang, PF; Barr, AR; Bakal, C; Kanemaki, MT; Lamond, AI; Novak, B; et al. (EMBO Press, 2020)
Two mitotic cyclin types, cyclin A and B, exist in higher eukaryotes, but their specialised functions in mitosis are incompletely understood. Using degron tags for rapid inducible protein removal, we analyse how acute depletion of these proteins affects mitosis. Loss of cyclin A in G2‐phase prevents mitotic entry. Cells lacking cyclin B can enter mitosis and phosphorylate most mitotic proteins, because of parallel PP 2A:B55 phosphatase inactivation by Greatwall kinase. The final barrier to mitotic establishment corresponds to nuclear envelope breakdown, which requires a decisive shift in the balance of cyclin‐dependent kinase Cdk1 and PP 2A:B55 activity. Beyond this point, cyclin B/Cdk1 is essential for phosphorylation of a distinct subset of mitotic Cdk1 substrates that are essential to complete cell division. Our results identify how cyclin A, cyclin B and Greatwall kinase coordinate mitotic progression by increasing levels of Cdk1‐dependent substrate phosphorylation.